PERSEPSI MAHASISWA UNIVERSITAS RIAU TERHADAP TUGAS DAN WEWENANG KOMISI PEMBERANTASAN KORUPSI (KPK) - Muhammad Fauzi; Sri Erlinda; Gimin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research was motivated by the abuse of authority by apparatus of the central government or local government in Indonesia. With the law of enforcement of the Corruption Eradication Commission (KPK), this proves that the duties and authority of the Corruption Eradication Commission (KPK) is deemed bad. With the background of the establishment of the KPK as the eradication and prevention of corruption in order to improve public services in Indonesia. So the writer was conducted a research entitled “Riau University Students’ Perception of the Duties and Authority of Corruption Eradication Commission (KPK)”. The formulation of the problem in this research “is how the Riau University Students’ perception on the duties and authority of KPK?”. This was aimed to know the Riau University students’ perception on the duties and authority of KPK. The sample in this research was selected by employing purposive sampling. There were 180 respondents and each faculty has 20 respondents. The data collection instrument was questionnaire and interview. There are fourteen (14) questions which are seven (7) questions for the duties of KPK and seven (7) questions for authority of KPK. Based on the data analysis, the students’ perception on the duties of KPK was rated as good with the percentage 61,51% and the percentage for authority of KPK was 68,74%. Based on both of indicators, the duties and authority of KPK, the average percentage was 60,24%, the respondents answered “good” in the range 50,01%-75%. It can be concluded that the duties and authority of KPK in good category. Keywords : Studen’s, Duties and Authority of Corruption Eradication Commission.